The Role of Environmental Social Governance (ESG) in Moderating the Influence of Financial Factors on Stock Returns in the Property and Real Estate Industry - Agustino, Deni; Kurniasih , Augustina (International Journal Labs, 2025)
This study aims to analyze the effect of liquidity (CR), leverage (DER), profitability (ROA), and sales growth (SG) on stock returns, with Environmental Social and Governance (ESG) as a moderator variable. The research data is panel data from 13 companies listed on the Indonesia Stock Exchange and have reports related to ESG scores during the 2020-2023 period. Data analysis was carried out descriptively and inferentially. Inferential analysis uses a panel data regression approach, this analysis involves moderating variables into the regression model to test the interaction between independent and moderating variables whether they have a significant influence on the dependent variable.ESG as a moderator variable is used to moderate the independent variable against the dependent variable whether it strengthens or weakens. The results of the model selection test show that the common effect model (CEM) is the best model. The results of the study found that CR, ROA, and SG have a positive and significant effect on stock returns, while DER and ESG do not have a significant effect on stock returns. In addition, ESG does not act as a moderator variable in the relationship between CR, DER, ROA, and SG with stock returns.